Never Lose Hope on Your Community Improvement in Religion: Issues of Takfir (Infidel) and Condemnation among American Muslims - Adesokan, Abdurrahman Toyese; Abdul Hamid, Faisal @ Ahmad Faisal; Yusof, Abdullah; Ali @ Mat Zin, Aizan (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
With the recent spread of Islam in the west and United States of America, it is now necessary to analyze the best gradual method of presenting the teachings of Islam to people in the light of objectives of Sharia. The expansion of Islam is of tactical and strategic planning of the part of Prophet Muhammed. Believers should be relieved from the fear of harsh methods that can make them lose hope in themselves and their community. The work will focus on the human feelings, and the simplicity of Islamic teachings and its effect of rising new generation within the Islamic schools. Contents will be derived from the Quran, the traditions of the Prophet and the sayings of the scholars based on the teachings. Prophet Muhammed said: “Verily, the religion is easy, and no one burdens himself in religion except that it overcomes him, so be moderate, seek closeness to Allah, give glad tidings and gain strength for worship in the morning and the night”. Muslim leaders in Houston along with the political leaders in America and many non-Muslims confirmed the simplicity of Islam. The result of this work will lay emphasis on the importance of wisdom and beautiful admonitions. It will enhance Islamic schools’ perfect way to choose the syllabus that will serve the community better.